Measurement of W(+/-)Z production in proton-proton collisions at root s=7 TeV with the ATLAS detector - Onofre, A. (2012)
A study of W±Z production in proton-proton collisions at √s=7 TeV is presented using data corresponding to an integrated luminosity of 4.6 fb−1 collected with the ATLAS detector at the Large Hadron Collider in 2011. In total, 317 candidates, with a background expectation of 68±10 events, are observed in double-leptonic decay final states with electrons, muons and missing transverse momentum. The total cross-section is determined to be σtotWZ=19.0+1.4−1.3(stat.)±0.9(syst.)±0.4(lumi.) pb, consistent with the Standard Model expectation of 17.6+1.1−1.0 pb. Limits on anomalous triple gauge boson couplings are derived using the transverse momentum spectrum of Z bosons in the selected events. The cross-section is also presented as a function of Z boson transverse momentum and diboson invariant mass.